Building and other construction workers (regulation of employment and conditions of service) act, 1996 (New Delhi, 2012)
In building and other construction works more than eight million workers are engaged throughout the country, These workers are one of the most vulnerable segments of the unorganised labour in India. Their work is of temporary nature, the relationship between employer and the employee is temporary, working hours are uncertain. Basic amenities and welfare facilities provided to these workers are inadequate. Risk to life and limb is also inherent. In the absence of adequate statutory provisions to get the requisite information regarding the number and nature of accidents was quite difficult and due to this to fix responsibility or to take corrective measures was not an easy job. Although the provisions of certain Central Acts were applicable to the building and other construction workers yet a need was felt for a comprehensive Central Legislation for regulating the safety, welfare and other conditions of service of these workers. In pursuant to the decision of the 41st Labour Ministers' Conference held on 18th May, 1995, the Committee of State Labour Ministers had expressed its consensus for the Central Legislation on this subject. In order to regulate the employment and conditions of service of building and other construction workers and to provide for their safety, health and welfare measures the Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Ordinance, 1995 (Ord. 14 of 1995) was promulgated by the President on 3rd November, 1995 as the Parliament was not in session. To replace this Ordinance a Bill was introduced in the Lok Sabha on 1st December, 1995. Since the Bill could not be taken up for consideration it lapsed. On 5th January, 1996 the President promulgated the Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Ordinance, 1996 (Ord. 3 of 1996). To replace this Ordinance a Bill was introduced in the Parliament which could not be passed and the President promulgated the Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Second Ordinance, 1996 (Ord. 15 of 1996) on 27th March, 1996. As this Ordinance could not be replaced by an Act of Parliament the President promulgated the Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Third Ordinance, 1996 (Ord. 25 of 1996) on 20th June, 1996. In order to replace this Ordinance the Building and Other Construction Workers (Regulation of Employment and Conditions of Service) Bill was introduced in the Parliament.
Keywords: "Regulation of employment and conditions of service act,"